The Role of CRM-Based Information Systems and Service Quality in Enhancing Customer Loyalty of MSMEs in Padang - Clarissa, Cindy; Veri, Jhon (UPI YPTK Journal of Business and Economics, 2025)
The study aims to discover the influence of CRM-based information systems and service quality on MSMEs' customer loyalty in Padang City. The unit of analysis is Micro, Small, and Medium Enterprises (MSMEs) in Padang City. The study utilised primary data obtained through the questionnaire. Sampling technique by using quota sampling. 120 questionnaires from MSMEs were returned as a final sample. Data were analysed using multiple regression analysis performed by SPSS software. The result shows that CRM-based information systems significantly influenced customer loyalty in Padang City. Service quality significantly influenced customer loyalty in Padang City. The findings of this study have several important implications; MSMEs should invest in and adopt digital CRM solutions to improve customer interactions, data management, and personalised services, ultimately leading to increased customer retention. MSMEs should improve their service standards continuously. Enhancing responsiveness, reliability, and customer engagement can help build stronger customer relationships and trust.